1983
DOI: 10.1111/j.1365-2125.1983.tb01547.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcoholic cirrhosis on the activities of microsomal aldrin epoxidase, 7‐ethoxycoumarin O‐de‐ethylase and epoxide hydrolase, and on the concentrations of reduced glutathione in human liver.

Abstract: The University of Newcastle-upon-Tyne, Newcastle-upon-Tyne 1 Activities of the microsomal mono-oxygenases 7-ethoxycoumarin O-de-ethylase (EOC) and aldrin epoxidase (AE), together with microsomal epoxide hydrolase (EH) activity and concentrations of reduced glutathione (GSH) have been measured in liver from patients with alcoholic cirrhosis and in normals. 2 Activities of both mono-oxygenases were significantly reduced in alcoholic cirrhosis. EOC activity (pmol 7-OH coumarin formed/mg microsomal protein/min) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…There was a three fold variation in enzyme activity in control subjects, and this was even greater in some of the disease groups. We have previously noted similar variation in both normal liver and in alcoholic cirrhotics, using both 7-ethoxycoumarin and aldrin as probe substrates (Woodhouse et al, 1984(Woodhouse et al, , 1983, and Boobis et al (1980) found that aryl hydrocarbon hydroxylase activity in human liver biopsies varied more than three fold. The main finding of the study, however, is that the histologically graded severity of the liver disease appears to be a relatively minor determinant of 7-ethoxycoumarin O-de-ethylation in PBC.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…There was a three fold variation in enzyme activity in control subjects, and this was even greater in some of the disease groups. We have previously noted similar variation in both normal liver and in alcoholic cirrhotics, using both 7-ethoxycoumarin and aldrin as probe substrates (Woodhouse et al, 1984(Woodhouse et al, , 1983, and Boobis et al (1980) found that aryl hydrocarbon hydroxylase activity in human liver biopsies varied more than three fold. The main finding of the study, however, is that the histologically graded severity of the liver disease appears to be a relatively minor determinant of 7-ethoxycoumarin O-de-ethylation in PBC.…”
Section: Discussionsupporting
confidence: 52%
“…Biopsies were homogenised and microsomal fractions prepared as previously described (Woodhouse et al, 1983). Enzyme activity was determined by measuring the rate of formation of 7-hydroxycoumarin from the substrate, 7-ethoxycoumarin (Greenlee & Poland, 1978).…”
Section: Assay Of 7-ethoxycoumarin O-de-ethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of reduced activity in patients with severe alcoholic liver disease compared to controls is compatible with our previous work (Woodhouse et al 1983(Woodhouse et al , 1984, in which the activities of the microsomal monooxygenases, aldrin epoxidase, and 7-ethoxycoumarin 0-deethylase, were shown to be reduced in patients with severe alcoholic cirrhosis. The present study is of particular interest because the cytochrome P-450 forms involved are probably responsible for the activation of a large number of environmental carcinogens to their ultimate carcinogenic form.…”
Section: Discussionsupporting
confidence: 91%
“…Ethoxycoumarin-O-deethylation (ECOD) ECOD was measured as described previously (Woodhouse et al, 1983) at high (1000 FM) and low (5 FM) substrate concentrations.…”
Section: Ethoxyresorufin-o-deethylation (Erod) Assaymentioning
confidence: 99%